PERAN MEDIASI KINERJA KEUANGAN DALAM PENGARUH KEBIJAKAN PENDANAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI DI BURSA EFEK INDONESIA - Senewe, Fika Olivia; Arifin, Andi Harmoko; Mubarok, Faizul (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the effect of funding policy on firm value with financial performance as a mediating variable in manufacturing companies in the consumer goods industry listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. This study uses a quantitative approach with an associative method to test the relationship between variables using panel data analysis processed through the Eviews12 and SmartPLS applications. The independent variable in this study is funding policy proxied by Debt to Equity Ratio (DER), while financial performance as a mediating variable is proxied by Return on Equity (ROE), and firm value as a dependent variable is proxied by Price to Book Value (PBV). The research sample was obtained through a purposive sampling method and included 26 companies that met the criteria with a total of 130 observations over five years. The results of the study indicate that (1) funding policy has a negative effect on financial performance, (2) funding policy has a negative effect on firm value, (3) financial performance has a positive effect on firm value, and (4) financial performance is proven to mediate the effect of funding policy on firm value. These findings confirm that a disproportionate funding structure can depress profitability, thereby lowering the perceived value of a company in the market. While improved financial performance can strengthen the value of companies in the consumer goods industry sector on the Indonesia Stock Exchange (IDX). "The Mediating Role of Financial Performance in the Influence of Dividend Policy and Investment Decisions on Firm Value in Manufacturing Companies in the Consumer Goods Industry Sector on the Indonesia Stock Exchange."